Nutrition Availability and Salt Content In Aquaconic Cultivation System of Kangkung and Lele Fish Plant - Setyo Budi Santoso; Hadi Suhardjono; Guniarti (Agricultural Science, 2020)
Urban vegetable cultivation using the aquaponic system can be considered as a future agricultural consideration because fish manure and fish food residues can become nutrients for plants after being decomposed by micro-organisms in pond water. The study aims to determine the availability of nutrients and dissolved salts in catfish ponds for 5 weeks before harvest and the growth of water spinach plants (Ipomoea aquatica) in aquaponic cultivation systems. The study was conducted at the Greenhouse UPN Veteran in East Java using 4 catfish ponds as a test given EM4 probiotic solution. Probiotics EM4 given as much as 20 ml per pool as a decomposer. Control is done by planting water spinach on soil media. Observations are carried out every week. The results showed 1). Water spinach plants planted with aquaponic systems have poor growth compared to those planted using soil media. 2). Nutrient concentration and salt content in pool water always increase during the study.